Coping with the future : theories and practices of divination in East Asia - Lackner, Michael, 1953- (Sinica Leidensia, 2018)
Coping with the Future: Theories and Practices of Divination in East Asia offers insights into various techniques of divination, their evolution, and their assessment. The contributions cover the period from the earliest documents on East Asian mantic arts to their appearance in the present time. The volume reflects the pervasive manifestations of divination in literature, religious and political life, and their relevance for society and individuals. Special emphasis is placed on cross-cultural influences and attempts to find theoretical foundations for divinatory practices. This edited volume is an initiative to study the phenomena of divination across East Asian cultures and beyond. It is also one of the first attempts to theorize divinatory practices through East Asian traditions.